Optimization of Real-Time Operational Data Monitoring Through Installing The Device on the Unit - Sastradi, Handy; Saputro, Angga Margi; Maulana, Muhammad Fachri (Al Makki Publisher, 2023)
Coal is the largest natural resource in Indonesia and has a vital role in global energy in various industries. PT Putra Perkasa Abadi (PPA), a mining contractor in South Kalimantan, faces problems with manual reporting being late and prone to errors. This project aims to speed up the digitization of the reporting process by providing PPA Team devices in the Heavy Equipment (A2B) and Support units. This is in line with the commitment of the PPA Mining Work Safety, Environment and Quality (K3PLM) Policy. This implementation starts from observation and data collection by selecting SS6 devices and creating designs for each unit. Continue with device installation, analyze problems, and repair installation. Following, carry out trials and socialize the use of the device to operators. With the implementation of the PPA Team application on the SS6 Monitor, Operators at PPA can independently input data on operational activities, including check-in / check-out units. It will reduce paper in operational reporting by providing an SS6 Monitor device. In addition, cost calculations can be adjusted to actual data, and operators can monitor unit Hour Meter (HM) data and operational activities directly on the SS6 Monitor. This reduces the duration of data input time, but also reduces the intensity of crowding on communication radios, and minimizes data input errors. Therefore, optimizing operational monitoring at PPA by installing devices on units can increase efficiency, including HM input for cost calculations, efficient unit HM reporting, fast check-in / check-out processes, digital unit breakdown reporting for more efficient communication, rapid digital validation of P2H, and moving from paper forms to digital tools for more sustainable work practices.